Reply to comments on the solidification of gray cast iron - Rivera, Graciela Leonor (2005)
The discussion is focused on the differences between what Hillert calls “classical work in the field” and the more recent bibliography. The authors prove that the role of austenite dendrites on the solidification of eutectic and hypereutectic gray iron has been overlooked over recent years, and that the picture of the solidification mechanism was not clear.